PELATIHAN PENERAPAN KEBIJAKAN AKUNTANSI PEMERINTAH KABUPATEN ROKAN HILIR - Azlina, Nur; Iznillah, Muhammad Luthfi; Nasir, Azwir; A, Al Azhar; Desmiyawati; Bahri, Fathul; Amri, Taqiyuddin (Universitas Mataram, 2024)
With the issuance of regulations requiring the implementation of the Regional Government Information System (SIPD), the Rokan Hilir local government made adjustments to these changes by issuing a Regent Regulation on the Rokan Hilir Regency Government Accounting Policy. Then human resources in charge of regional financial management in Rokan Hilir Regency must be able to improve their competence by conducting training in the application of Regional Government Accounting Policies according to Permendagri 77 of 2020. The purpose of this activity is to provide assistance in the form of training on the Application of Rokan Hilir Regency Government Accounting Policies in 2022 in accordance with Permendagri 77 of 2020 to human resources who prepare financial reports in SKPD and PPKD of the Rokan Hilir Regency Government. Activities are carried out using the lecture method which is adjusted to the material that has been prepared. The activity was carried out on August 14, 2023 with 25 participants from the Regional Financial and Asset Management Agency (BPKAD) and Rokan Hilir Regency Accounting Personnel. The activity has been carried out well and adds new knowledge to the Human Resources of financial management in Rokan Hilir Regency so as to create accountable financial management in accordance with the mandate of the law. accountable financial management in accordance with the mandate of the law.